KEANEKARAGAMAN CAPUNG (ODONATA) DI TAMAN MINI INDONESIA INDAH DAN TAMAN MARGASATWA RAGUNAN, DKI JAKARTA, INDONESIA - Syarifah, Eva Bai; Fitriana, Narti; Wijayanti, Fahma (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
The dragonfly conservation needs to be protected by maintaining the existence of their living place which in a large number is waters. This research was conducted using survey method at Taman Mini Indonesia Indah and Ragunan Zoo, South Jakarta. The sampling was done using purposive sampling by selecting 3 habitat around the waters in Taman Mini Indonesia Indah (TMII) and another 3 habitats around the water in Taman Margasatwa Ragunan (TMR). The line transec was made drawing a line a long 50 m in northern, 50 m in shouter, 50 m in western and 50 m in eastern of the waters or the lake which each wide was 1 meter to the left and 1 meter to the right. Based on the result of this research, the dragonfly diversity has two different families which are Libellulidae and Ghomphidae. Family of Libellulidae in this research area has five different species which are Orthetrum sabina, Pantala flavescens, Orthetrum testaceum, Neurothemis terminata, Brachythemis contaminate. Meanwhile, Family of Ghomphidae has one species which is Ictinogomphus decoratus. Indeks value of diversity in TMII shows that the dragonfly relatively high and TMR it’s relatively low. Indeks value of distribution in two location is about over 0,81 it means that the distribution of dragonfly species is relatively high